Ed Wood [videorecording (DVD)] - Depp, Johnny; Landau, Martin, 1928-2017; Parker, Sarah Jessica; Arquette, Patricia, 1968-; Murray, Bill, 1950 September 21-; Burton, Tim, 1958- (Touchstone Home Entertainment, 2004)
A stranger-than-fiction true story of the early career of Edward D. Wood, Jr., the once voted worst movie director of all time. Wood was the auteur behind Glen or Glenda? and Plan 9 from outer space, and it is during the making of these two no-budget flicks that Wood is profiled.